Analysis of Calibration and Validation of Road Roughness Survey Equipment (Hawkeye 2000) Based on SNI 3426:2022 - Dody Kusmana; Ade Kurniawan; Ivany Sarief; Cecep Deni Mulyadi (Jurnal Penelitian Pendidikan IPA, 2026)
Road roughness measurement using the International Roughness Index (IRI) plays a critical role in road asset management, influencing maintenance prioritization and budget allocation. However, discrepancies between instruments may introduce bias without proper calibration. This study aims to analyze the calibration and validation of the Hawkeye 2000 as a Digital Laser Profiler for IRI measurement based on SNI 3426:2022. Calibration was conducted using a Walking Profilometer as the reference instrument, followed by validation on five test segments (SP1–SP5) with lengths of 100–500 meters under three speed variations (40, 50, and 60 km/h). The results show that the Hawkeye 2000 meets the requirements of SNI 3426:2022, with coefficients of determination (R²) of 0.9819 (left), 0.9850 (right), and 0.9820 (combined), indicating high accuracy. The coefficient of variation (CV) ranges from 0.0159 to 0.0241 (<5%), reflecting high precision. Calibration parameters (A = 0.9956; B = −0.0093) are within acceptable limits. The instrument also demonstrates consistent performance across different speeds. In conclusion, the Hawkeye 2000 is reliable for field IRI measurement, although further studies are needed to consider broader road conditions and external factors.